India's technological climate: a harbinger in resolving and reducing the carbon footprint. (2018) - Christie, Luke Gerard; Kumar, Gajendra
Research in artificial intelligence and cognitive computing (simulation of human thought processes in machines involving self-learning systems and processes that efficiently use pattern recognition such as detecting voice, or acquiring data (data mining) and imitating human thoughts in machines) is an evolutionary and innovative field acquiring knowledge from liberal arts, humanities such as management science, philosophy, psychology. The need to rely on these disciplines is of vital importance and strategic value in today's technology up-gradation as robots are designed to think and behave like human-beings. Robotic technology can assess and solve problems through the aid of human intervention and support. Issues that are of a laborious nature can be solved through machine technology and processes or machines and humans must work together to solve larger problems of which the dire need is where humans and machines need to work together in solving problems of global warming and climate change.